Significant sodium plasma reduction after half-ironman triathlon in Brazilian triathletes - Mendonça, M. B.; Bielavsky, M.; Barbosa, F. C. R. (Journal of Human Sport & Exercise, 2009)
Hypontremia defined as a serum concentration below 135 mmol/L (1 mmol/L - 1mEq/L). The aim of the present study was to analyze the effects of half-ironman triathlon on serum sodium concentration in Brazilian triathletes. Significant changes after triathlon completion was found pre = 141.72± 0.75 mmol/L; post= 138.37± 0.72 mmol/L (P=0.018). Was not found significant correlation between sodium plasma concentrations after the competition with the finishing time. In conclusion, the results presented herein, showing significative reduction in the sodium plasmatic concentrations remain between normal ranges.